2013
DOI: 10.1073/pnas.1303058110
|View full text |Cite
|
Sign up to set email alerts
|

EGF shifts human airway basal cell fate toward a smoking-associated airway epithelial phenotype

Abstract: The airway epithelium of smokers acquires pathological phenotypes, including basal cell (BC) and/or goblet cell hyperplasia, squamous metaplasia, structural and functional abnormalities of ciliated cells, decreased number of secretoglobin (SCGB1A1)-expressing secretory cells, and a disordered junctional barrier. In this study, we hypothesized that smoking alters airway epithelial structure through modification of BC function via an EGF receptor (EGFR)-mediated mechanism. Analysis of the airway epithelium revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 51 publications
8
99
1
Order By: Relevance
“…Nitric oxide, which enhances viral clearance and limits RV-stimulated proinflammatory cytokines (39,40), is produced primarily by ciliated cells in the airway epithelium (41), and these cells are absent in injured/regenerating epithelium. Finally, undifferentiated polarized cells also showed higher expression of EGFR than did mucociliary-differentiated cells (37,42). Therefore, it is likely that RV, which is not cleared effectively in injured/regenerating airway epithelial cell cultures, may activate the EGFR that is already highly expressed in injured/regenerating cells, thereby prolonging barrier dysfunction and promoting abnormal differentiation.…”
Section: Original Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Nitric oxide, which enhances viral clearance and limits RV-stimulated proinflammatory cytokines (39,40), is produced primarily by ciliated cells in the airway epithelium (41), and these cells are absent in injured/regenerating epithelium. Finally, undifferentiated polarized cells also showed higher expression of EGFR than did mucociliary-differentiated cells (37,42). Therefore, it is likely that RV, which is not cleared effectively in injured/regenerating airway epithelial cell cultures, may activate the EGFR that is already highly expressed in injured/regenerating cells, thereby prolonging barrier dysfunction and promoting abnormal differentiation.…”
Section: Original Researchmentioning
confidence: 98%
“…Chronic EGFR activation by Sendai virus induces goblet-cell metaplasia in welldifferentiated airway epithelial cells by promoting survival and transdifferentiation of ciliated cells to goblet cells (36). EGFR activation in basal airway epithelial cells reduces the expression of genes involved in ciliogenesis and the secretory phenotype, shifting cells toward squamous and EMTlike phenotypes (37). In this study, we found that RV, by activating EGFR, inhibits the expression of E-cadherin and CRB3, each of which regulates the polarization of cells, the event that dictates subsequent cell differentiation (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…Among these questions are whether the chronic inflammatory conditions prevalent in disorders such as asthma, smoking-associated COPD, and CF result in epigenetic changes in basal cells. Such changes might make them inherently more likely to differentiate into secretory rather than multiciliated cells, or into squamous versus mucociliary epithelium, even when pathological conditions revert to normal (Shaykhiev et al, 2013).…”
Section: Organoids From Human Basal Cellsmentioning
confidence: 99%
“…Immunohistochemical evidence suggests that epidermal growth factor receptor (EGFR) signaling plays a role in airway diseases including asthma (3,15), chronic obstructive pulmonary disease (53), chronic bronchitis (28,44), and cystic fibrosis (51). Furthermore, increased EGFR expression was detected in basal cells located in regions of repairing epithelium in asthmatic patients (33,45) and in basal cells of chronic smokers (25,40). A specific role for EGFR in basal cell proliferation is supported by the finding that successful culture of basal cells from normal adult human bronchial and nasal tissue (26,55) and from hamster (54), rat (46), and mouse trachea require epidermal growth factor (EGF).…”
mentioning
confidence: 99%